Characterization and performance analysis of generalized BOC modulations for GNSS. Issue 1 (13th February 2019) - Nunes, Fernando D.; Sousa, Fernando M. G.; Leitão, José M. N.
Abstract: Novel modulations, based on the binary chirp waveform, are proposed as generalizations of binary offset carrier (BOC) schemes. They allow enhancement of the performance of Global Navigation Satellite System (GNSS) receivers affected by Gaussian noise, multipath, and interference. Adequate selection of parameters enables efficient use of the channel bandwidth to enlarge the Gabor bandwidth. Schemes characterized by autocorrelations with small secondary peaks are obtainable, permitting minimization of the probability of code acquisition with incorrect code phase and reducing the probability of false code‐locks in tracking mode. Increased robustness to multipath and interference also occurs. These advantages make the proposed modulation schemes promising candidates for future navigation signals.